2019
DOI: 10.11124/jbisrir-2017-003889
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for defining and assessing nursing informatics competencies: a scoping review protocol

Abstract: Review question: How are nursing informatics competencies defined or assessed in the literature?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…This is consistent with previous findings. Nursing professionalism affects the perception of patient privacy protection, such as protection of patients’ privacy and personal information [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The findings confirmed that the higher the nursing professionalism, the higher the protection of patient privacy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with previous findings. Nursing professionalism affects the perception of patient privacy protection, such as protection of patients’ privacy and personal information [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The findings confirmed that the higher the nursing professionalism, the higher the protection of patient privacy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were limitations in comparing the results of this study with other studies that confirmed the relationship between nursing professionalism and informatics competency due to the scarcity of such studies. Previous studies found that nursing professionalism showed a significant positive correlation with patient information management and information literacy (the ability to collect, interpret, and judge necessary information correctly), which is a similar concept to a sub-concept of nursing informatics competency [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Nursing professionalism includes practical competency along with ethical standards in a rapidly changing medical environment [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De esta información se observa que cuatro áreas no tuvieron respuestas: Informática de Enfermería, Salud masculina, Salud de inmigrantes y Refugiados; esto despertó el interés del equipo de la RCE en conocer cómo estas áreas afectan a las personas de los países que respondieron. Como tendencia actual y futura de la ciencia de Enfermería, la competencia en informática de Enfermería sostiene otras competencias importantes, como la colaboración interpersonal, la prestación de atención centrada en el paciente y la práctica basada en la evidencia para la calidad de la atención 8 . Asimismo, la investigación sobre la salud masculina es una prioridad epidemiológica, ya que ha reducido la esperanza de vida de los hombres en la región de las Américas 9 .…”
Section: Salud De Los Hombresunclassified